The Effect of ERCoRe Learning Model Assisted Kumatalibi.com Media on Creative Thinking Skills in Ecosystem - Naufal Hilmi, Nur Muhammad; Maspupah, Meti; Hartati, Sri (Jurnal BIOEDUIN : Program Studi Pendidikan Biologi, 2026)
Creative thinking skills are becoming increasingly important in the era of Industry 4.0, particularly in addressing challenges in biology learning, which often involves misconceptions. This study aims to analyze the effect of the ERCoRe Learning model assisted by the kumatalibi.com media on students’ creative thinking skills in the Ecosystem topic. The research method employed is a quasi-experimental design using a pretest-posttest control group. The experimental class applied the ERCoRe Learning model, while the control class used the Problem-Based Learning (PBL) model. The research instrument consisted of tests based on indicators of creative thinking skills. The results showed a significant effect of implementing the ERCoRe Learning model assisted by kumatalibi.com on improving students' creative thinking skills, with an effect size score of 0.725 based on Cohen’s test, which falls into the high category. Students also showed positive responses toward the use of the model and media in learning. This study recommends the use of ERCoRe Learning as an alternative constructivist-based innovative learning model to enhance creative thinking skills in the classroom.